2003
DOI: 10.1086/376509
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Immune Activation Marker Changes in Human Immunodeficiency Virus (HIV)–Seropositive and High‐Risk HIV‐Seronegative Women Who Use Illicit Drugs

Abstract: The majority of natural history studies of human immunodeficiency virus (HIV) infection have immune and viral parameters in men. Data demonstrating that women have lower HIV-1 RNA levels than men at the same CD4 cell counts have raised the question of immunologic differences in HIV-seropositive women. This study describes levels and changes in phenotypic markers of immune maturity, function, and activation in the CD4 and CD8 cell subsets in HIV-seropositive and high-risk HIV-seronegative women. Our primary hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
2
22
0
2
Order By: Relevance
“…This report complements a larger WIHS study (20), which found that immune activation was driven by HIV-1 infection, and not by illicit drug use. Conditions affecting HIV-1 replication in local compartments such as cell type, cytokine profile, or inflammation, may indeed exert selective pressures leading to compartmentalization, and additional in vivo analyses are needed (13,14).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This report complements a larger WIHS study (20), which found that immune activation was driven by HIV-1 infection, and not by illicit drug use. Conditions affecting HIV-1 replication in local compartments such as cell type, cytokine profile, or inflammation, may indeed exert selective pressures leading to compartmentalization, and additional in vivo analyses are needed (13,14).…”
Section: Discussionsupporting
confidence: 78%
“…We studied 12 participants in the BronxManhattan and Brooklyn, New York sites of the Women's Interagency HIV Study (WIHS), a multicenter, prospective study of HIV-1 infection of women (15,20). Participants were interviewed and examined semiannually; blood and gynecologic specimens including cervicovaginal lavage (CVL) were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, previous WIHS research has shown that self-reported medication use is consistent with objective measures of HIV outcome, such as CD4þ T-cell count, HIV viral load, and self-reported physical functioning, 36 and that self-reported substance use has a high degree of validity using a toxicology analysis for cocaine and opiates on a subset of WIHS participants. 37 Also, participants used a variety of CAM modalities with low frequency of specific modalities. By combining CAM modalities into CAM categories, some of the specificity that specific modalities might have allowed were lost.…”
Section: Discussionmentioning
confidence: 99%
“…These studies could not have been done in the context of the controlled regimens and adherence requirements necessary for clinical trials. Collaborative work on coinfections such as hepatitis C (3) and human papillomavirus (21,23,18) in the HIV-positive cohort; on the risk of developing other comorbidities related to HIV and antiretroviral therapies, such as cancer (12), diabetes (13), and lipodystrophy (22); and on IVDU (17) and changes in sexual risk behaviors (24) have benefited largely by having a control group of HIVnegative women who match the infected cohort in sociodemographic and behavioral characteristics as well as by having both groups of HIV-positive women: those treated with HAART and those who are HAART naïve.…”
Section: Wihs Strengths and Limitationsmentioning
confidence: 99%